Essays on the Chilean economy - Mamalakis, Markos; Reynolds, Clark Winton (Homewood, Ill., R.D. Irwin, 1965)
This volume, sponsored by Yale Growth Center, consists of two long essays: "Public Policy and Sectoral Development: A case study of Chile, 1940-58," by Mamalakis, and Development Problems of an Export Economy: The Case of Chile and Copper," by Reynolds. The reader is well advised to begin and perhaps terminate with the second essay, an excellent case study of the problem of integrating the export sector of a dual economy.
"Portions of these essays originated in doctoral dissertations at Berkeley."
Includes bibliographical references.
rpm 14/06/2017
Loans
Keywords: Industries; Copper industry and trade; Copper industry and trade--Chile.; Chile--Economic policy; Chile